Decision-making criteria for medicine reimbursement in Slovenia: an expert panel discussion - Andreja Detiček; Andrej Janzic; Igor Locatelli; Mitja Kos (BMC, 2018)
Abstract Background Rational and transparent Health Technology Assessment and reimbursement decision-making are crucial for healthcare system sustainability. A part of the reimbursement process are decision-making criteria which should be clearly defined. Methods The study aimed to obtain an insight into understanding and relevance of potential criteria for the medicine reimbursement decision-making process in Slovenia. A semi-structured guided focus panel was performed in June 2017 with five Slovenian experts covering principal healthcare system sectors. First, criteria understanding and relevance for medicine reimbursement decision-making were discussed. Second, healthcare priorities and societal values affecting decision-making were debated. The analysis was carried out with NVivo 11 by two independent researchers who coded the verbatim transcript in three coding steps based on the experts' interpretations and original ideas. Results Seven decision-making criteria were derived. Among those, the impact a disease has on the lives of patient family and caregivers and the indirect medicine benefit for them were new aspects comparing to the existing criteria set in Slovenia. The experts expressed that the same decision-making criteria are relevant for evaluating any health technology, allowing for different criteria weights. They also suggested a system that would allow re-evaluation of reimbursement decisions once real-world clinical data are available. Conclusions As proposed by the international frameworks and tools, the Slovenian healthcare experts consider including multiple aspects more ethical and comprehensive than considering a single criterion, e.g. cost-effectiveness, existing in some healthcare systems. They recognize that in the existing decision-making process, health perspectives of the public represent a largely missed aspect.